Clinical Pattern, Morphology and Treatment Modality of Basal Cell Carcinoma of Head and Neck Region: Analysis of 10 Cases - Parveen Mendiratta; Vandana Mendiratta; Roopak Aggarwal; Shailendra Pal Singh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Basal cell carcinoma is most common type of non-melanotic skin cancer. Causative agents are UV and ionizing radiation and chemicals. Nodular, pigmented, superficial, cystic and infiltrative are major subtypes. It is mainly treated by excision surgery in the form of wide local excision and reconstruction is done by various flaps. In our study 10 patients were included and found that carcinoma is commoner in old age female patients and mainly near right canthus of eyeball; treated with surgery which is well tolerated by all the patients.